Analisis dan Desain Sistem Informasi Administrasi Kegiatan Penelitian dan Pengabdian Masyarakat Menggunakan Metode Work System Framework dengan Pemodelan Unified Modeling Language - Afriansyah Afriansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
University can’t be separated from the Tri Dharma namely in the fields of education, research and community service. Institute for Research and Community Services Lancang Kuning University has launched a strategic framework for research through the Research Master Plan (RIP) and the Roadmap Research to support research results and superior quality. One of them by building an Information Systems Research Activities Administration and Community Services seeks to streamline the work of the staff LPPM and also makes it easy for researchers in particular lecturers and reviewers in their duties. In this system, the researchers register their proposals online. Furthermore, staff LPPM recaps the number of proposals on all types of grants that is then distributed to the reviewer to assess. Administration Information System Research Activities and Community Service is used method of analysis Work System Framework. Methods of work system framework, expected later able to provide a description of the process or activity system that uses information technology or other resources. Modeling design methodology using Unified Modeling Language (UML) and MySql database. Keywords : Information Systems, Administration, Work System Framework, UML